Correlates of newly diagnosed HIV infection among cisgender women sex workers and transgender women sex workers in Greater Kuala Lumpur, Malaysia. (June 2021) - Wang, Melinda; Lim, Sin How; Gibson, Britton A; Azwa, Iskandar; Guadamuz, Thomas E; Altice, Frederick L; Kamarulzaman, Adeeba; Wickersham, Jeffrey A
Globally, cisgender women sex workers (CWSWs) and transgender women sex workers (TWSWs) experience increased vulnerabilities to HIV infection. Unfortunately, there is limited data on the drivers of HIV infection in these two understudied populations, particularly in Southeast Asia. To better understand factors associated with HIV infection, we evaluated correlates of newly diagnosed HIV infection in these two populations in Greater Kuala Lumpur, Malaysia. A total of 469 women (CWSW: n = 283; TWSW: n = 186) were included in this study. Most participants who tested HIV+ were unaware of their infection (59.6%; n = 34/57). Separate binary and multivariable logistic regressions were conducted to identify correlates of newly diagnosed HIV in CWSWs and TWSWs. Among CWSWs, Chlamydia trachomatis (aOR = 5.66; p = 0.007) and lifetime use of ecstasy/MDMA (aOR = 5.34; p = 0.03) were associated with newly diagnosed HIV, while condomless vaginal sex with clients was associated with lower likelihood of HIV infection (aOR = 0.98; p = 0.01). Among TWSWs, being single (aOR = 6.76; p = 0.03), using mobile application to solicit clients (aOR = 25.33; p = 0.006), and having C. trachomatis infection (aOR = 88.22, p = 0.02) were associated with newly diagnosed HIV. Expansion of HIV/sexually transmitted infection screening is needed to increase detection of HIV and linkage to care for sex workers. Interventions to reduce HIV infection among CWSWs and TWSWs should be tailored to these populations' unique vulnerabilities.